2017
DOI: 10.1002/2016jg003722
|View full text |Cite
|
Sign up to set email alerts
|

Global relationship of fire occurrence and fire intensity: A test of intermediate fire occurrence‐intensity hypothesis

Abstract: Fire plays a significant role in global atmosphere and biosphere carbon and nutrient cycles. Globally, there are substantially different distributions and impacts between fire occurrence and fire intensity. It is prominent to have a thorough investigation of global relationship between fire occurrence and fire intensity for future fire prediction and management. In this study, we proposed an intermediate fire occurrence‐intensity (IFOI) hypothesis for the global relationship between fire occurrence and fire in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
4
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(7 citation statements)
references
References 38 publications
3
4
0
Order By: Relevance
“…Particularly, the percolation model shows that BA can drop dramatically once 50 %-60 % of the available fuel has burned, which is close to the maximum percentage of BA detected by both MCD64A1 and FireCCI41 products (Giglio et al, 2013;Chuvieco et al, 2016). The IFOI hypothesis, proposed by Luo et al (2017) to explain why fire occurrence is limited by fire intensity, can be interpreted as a direct consequence of percolation theory applied to fire-prone ecosystems.…”
Section: Discussionsupporting
confidence: 62%
See 1 more Smart Citation
“…Particularly, the percolation model shows that BA can drop dramatically once 50 %-60 % of the available fuel has burned, which is close to the maximum percentage of BA detected by both MCD64A1 and FireCCI41 products (Giglio et al, 2013;Chuvieco et al, 2016). The IFOI hypothesis, proposed by Luo et al (2017) to explain why fire occurrence is limited by fire intensity, can be interpreted as a direct consequence of percolation theory applied to fire-prone ecosystems.…”
Section: Discussionsupporting
confidence: 62%
“…Recent studies (Pausas and Ribeiro, 2013;Luo et al, 2017) have shown that fire occurrence, defined as the number of remotely detected active fires in units of time per unit of area, increases with fire intensity up until a threshold is reached (so-called intermediate fire occurrence-intensity (IFOI) hypothesis) above which occurrence decreases with increasing intensity. Since ignition and propagation are different processes and are not driven by the same climatic variables, it is necessary to go beyond fire occurrence and BA and to consider individual fire events.…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, the mean MODIS FRP is considerably higher in these latitudes than in the Tropics, especially in North America, Siberia, and Australia. This is consistent with previous studies based on satellite data of active fires that report a general inverse relationship between fire occurrence and observed FRP in most biomass burning ecosystems for intermediateand high-intensity fires (Giglio et al, 2006;Luo et al, 2017;Andela et al, 2019;Haas et al, 2022). Elevated FRP is typically associated with large and intense fires (Rogers et al, 2015), especially in temperate and boreal forested ecosystems where high fuel densities and fuel continuity in the landscape favour expanded, high-intensity, long-duration wildfires (Andela et al, 2019;Laurent et al, 2019).…”
Section: Influence From Fire Intensity and Plume Altitudesupporting
confidence: 93%
“…Particularly, the percolation model shows that BA dropped dramatically once 50-60% of the available fuel has burned, which is close to the maximum percentage of BA detected by both MCD64A1 and FireCCI41 products (Giglio et al 2013, Chuvieco et al 2016. The IFOI hypothesis, proposed by Luo et al (2017) to explain why fire occurrence is limited by fire intensity, can be interpreted as a direct consequence of percolation theory applied to fire-prone ecosystems.…”
Section: Discussionsupporting
confidence: 64%